Water diplomacy in action : contingent approaches to managing complex water problems - Islam, Shafiqul, 1960-; Madani, Kaveh (Anthem water diplomacy series, 2017)
Complex water problems cannot be resolved by numbers or narratives. Contingent and negotiated approaches are necessary for actionable outcome. In the face of a constantly changing array of interconnected water issues that cross multiple boundaries, the challenge is how to translate solutions that emerge from science and technology into the context of real-world policy and politics. Water Diplomacy in Action addresses this task by synthesizing two emerging ideas--complexity science and negotiation theory--to understand and manage risks and opportunities for an uncertain water future. Rooted in the ideas of complexity science and mutual gains negotiation, this edited volume shows why traditional systems engineering approaches may not work for complex problems, what emerging tools and techniques are needed and how these are used to resolve complex water problems.